2023
DOI: 10.1038/s41598-023-35396-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between heart rate variability and TNM stage, co-morbidity, systemic inflammation and survival in patients with primary operable colorectal cancer

Josh McGovern,
Stephen Leadbitter,
Gillian Miller
et al.

Abstract: High vagal nerve activity, reliability measured by HRV, is considered protective in cancer, reducing oxidative stress, inflammation and opposing sympathetic nerve activity. The present monocentric study examines the relationship between HRV, TNM stage, co-morbidity, systemic inflammation and survival in patients who underwent potentially curative resections for colorectal cancer (CRC). Time-domain HRV measures, Standard Deviation of NN-intervals (SDNN) and Root Mean Square of Successive Differences (RMSSD), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The ANS regulates many physiological processes, making it an excellent indicator of physiological abnormalities present in the human body. Many studies have previously observed lower HRVs among patients diagnosed with certain cancers like breast, colorectal, and lung [ 13 , 15 , 16 , 17 ]. Several studies have posited that the lower HRVs reflect abnormal upregulation of the SNS and/or PNS consequent to the increased innervation of sympathetic and parasympathetic fibers in cancerous tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The ANS regulates many physiological processes, making it an excellent indicator of physiological abnormalities present in the human body. Many studies have previously observed lower HRVs among patients diagnosed with certain cancers like breast, colorectal, and lung [ 13 , 15 , 16 , 17 ]. Several studies have posited that the lower HRVs reflect abnormal upregulation of the SNS and/or PNS consequent to the increased innervation of sympathetic and parasympathetic fibers in cancerous tumors.…”
Section: Introductionmentioning
confidence: 99%